(untitled) (Fiep Bulletin - online, 2019)
Introduction: The concept of body image can be defined as a multidimensional construct that broadly describes theinternal representations of body structure and physical appearance in relation to ourselves and others. Objectives: To evaluatethe perception of body image of the last period students (8th) of the Physical Education course of the Federal University of Piauí.Methods: The present study is characterized as quantitative, since it uses structured data taken from the questionnaires appliedto the composition of the sample. The sample consisted of 30 students of both sexes, aged 18 to 39 years, academics of the lastperiod of the Physical Education course of the Federal University of Piauí. We used the Body Shape Questionnaire (BSQ), DiPietro (2009) which is a self-completion test with 34 questions to be answered according to the LIKERT scale from 1 to 6 (1 -never, 2 - rarely, 3 - sometimes, 4 - often, 5 - very often, 6 - always). (2009). Results: According to the data presented, weevaluated that 83.3% d ACA dêmicos the last period have not distorted regarding their body image, however, even in smallquantities 4 (13.33%) had mild distortion 1 (3.33%) and moderate distortion 0 (0, 11%) severe Conclusion: it is concluded that thestudents studied are mostly satisfied with their body image, however, a small group presents some distortion, they are those whoare overweight ideal.